UPSKILLING AS A RETENTION ENGINE: BUILDING A FUTURE-PROOF WORKFORCE FROM WITHIN - Rizki Eka Putra; Rudy Hayadi; Oktavianti (RADJA PUBLIKA, 2026)
In an era of rapid technological disruption and skill obsolescence, organizations face the dual challenge of closing critical competency gaps and retaining top talent. This study investigates formal upskilling programs as a strategic retention engine, positing that investment in employee growth directly reduces turnover by fostering engagement, career path clarity, and a psychological contract of mutual investment. Using a mixed-methods approach, the research analyzed longitudinal HR data and conducted interviews at a multinational firm before and after implementing a structured, role-specific upskilling initiative. Results demonstrated a 40% reduction in voluntary turnover among participating employees and a significant increase in internal mobility and promotion rates. The discussion identifies key success factors: aligning skills with strategic business goals, providing clear internal career pathways, and ensuring managerial support for learning application. The study concludes that a strategic upskilling program, embedded within a broader talent development philosophy, is a powerful mechanism for future-proofing the workforce and building organizational resilience from within, transforming a cost center into a core retention and competitive advantage strategy.